Clinical, histological and high‐frequency ultrasonographic evaluation (50 MHz) of morphoea treated with ultraviolet A1 phototherapy. (4th July 2018) - Arisi, M.; Lorenzi, L.; Incardona, P.; Fusano, M.; Zanca, A.; Rossi, M. T.; Tomasi, C.; Calzavara‐Pinton, P. G.; Venturini, M.
Summary: Background: There are few studies in the literature correlating the ultrasonographic findings, clinical scoring systems or histological findings in morphoea after ultraviolet (UV)A1 phototherapy. Aims: To evaluate the quantitative and morphological aspects of high‐frequency ultrasonography in the treatment of plaque morphoea in response to UVA1 phototherapy, and to correlate these with clinical and histological scores. Methods: In total, 17 patients with morphoea were studied. Initially and at study end, high‐frequency ultrasonography (50 MHz) was performed on the edge of a morphoea lesion treated with UVA1 phototherapy. A quantitative and qualitative analysis of dermal features was performed and compared with the features of healthy skin. Skin biopsy specimens were obtained from lesions analysed at the beginning and end of the study, assessing dermal sclerosis and dermal inflammatory infiltrate and their distribution. Results: All affected skin showed a statistically significant increase in dermal thickness and hypoechogenicity, corresponding to a reduction in dermal density by ultrasonography compared with healthy skin. Morphological evaluation identified undulations of the dermis in 11 of 17 lesions (64.7%) and in 5 healthy skin areas (29.4%) ( P  = 0.08), while 'yoyo' figures were identified in 8 lesions (47%) but only 1 healthy skin area (5.9%) ( P  = 0.02). Ultrasonographic morphological analysis highlighted an improvement in dermal hyperechogenic bands and disappearance of yoyo figures after UVA1 treatment. Histology revealed a reduction in dermal sclerosis and inflammation, although this was not statistically significant. Conclusions: Ultrasonographic pattern analysis of morphoea is a suitable technique for monitoring UVA1 phototherapy response.